PENGARUH PIJAT BAYI TERHADAP FREKUENSI DAN DURASI MENYUSUI PADA BAYI USIA 0-6 BULAN DI POSYANDU MUKTI RAHAYU - TRI ENDAH WIDI LESTARI (Universitas Amikom Purwokerto, 2026)
Adequate breastfeeding frequency and duration are essential for optimal nutrition in infants aged 0–6 months. Infant massage is a non-pharmacological intervention that may improve breastfeeding behavior by stimulating the nervous and digestive systems. This study aimed to analyze the effect of infant massage on breastfeeding frequency and duration among infants aged 0–6 months at Mukti Rahayu Integrated Health Post. A quasi-experimental study with a one group pretest–posttest design was conducted involving 15 mother–infant pairs selected through purposive sampling. The intervention consisted of infant massage administered twice per week for one week, with each session lasting 30–45 minutes. Breastfeeding frequency and duration were measured using observation sheets. Data were analyzed using the Wilcoxon test. The results showed a significant increase in breastfeeding frequency (p=0.001) and breastfeeding duration (p=0.003) after the intervention. Infant massage was proven effective in improving breastfeeding patterns by enhancing infant comfort and physiological readiness to feed. Therefore, infant massage can be recommended as a promotive strategy to support breastfeeding success in early infancy at the primary health care level.